Inflation in Deutschland – eine empirische Bilanz - Susanne Erbe (Wirtschaftsdienst, 2024)
Measuring and explaining inflation is of great importance for political and economic decision makers. Various price indices are compiled at the national and European level, some of which show significantly different price trends due to their different focuses. The sharp rise in inflation rates since 2021 is primarily due to supply-side factors, in particular the sharp rise in energy prices. This is illustrated by the differences in the development of the VPI and core inflation. The price brakes on gas and electricity in particular have had a direct dampening effect on inflation, while the ECB's restrictive policy has had a more indirect effect. Although the inflation rate has fallen significantly by now, price pressure could come from a tightening of free trade due to increasing protectionism in the long term.
Keywords: E31; 330